Micronutrient contents in different parts of sunflower plants - Sfredo, Gedi Jorge; Sarruge, José Renato (Pesquisa Agropecuaria Brasileira, 2014)
To determine micronutrient contenta in different parta of sunflower planta (Heliantizus annuus L.), during growth, an experiment was carried out in Londrina (PR), Brazil, in a Dusky Red Latosol Eutrophic (Eustrustox). The experiment design was a randomized blocks, and six different rates of fertilizer were used to determine the greatest yielding one, in terms of grain and dry matter production, to be studied. By the results we can conclude that The lowest concentrations of Cu and Zn occurred near maximum dry matter production; Mn concentration was higher alter 42 days of emergence; B concentration was the greatest in receptacles and the lowest in achenes. For foliar diagnosis the following values may be used: Cu = 28 to 30 ppm; Mn = 180 to 220 ppm; Zn = 36 ppm; B = 88 to 102 ppm; and Fe = 200 ppm.